ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. I USIA 26 TAHUN DI PMB OKTA FITRIANA, S. ST KOTA SEMARANG - Sri Mularsih; Widyah Setiyowati (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are indicators used to measure maternal health status in a region. The purpose of the study is to provide comprehensive midwifery care carried out in a Continuity Of Care (CoC) manner. Qualitative research is presented in a descriptive exploratory manner with a study approach and examined with documentation studies. The sample in the study was Mrs. I, 26 years old, who will be studied from pregnancy, childbirth, BBL, postpartum and family planning. Case collection implementation from March - August 2025. The results of the study on Mrs. I's pregnancy ANC 11 times, normal delivery, BBL: female gender, BB: 3000 gr, PB: 47 cm, LK: 32 cm, LD: 32 cm, LILA: 11 cm. There were 2nd degree lacerations of the vaginal mucosa, perineal skin and perineal muscles. postpartum visits were 4x and the mother used MAL KB. Based on the study of Mrs. I's pregnancy care. I G1P0A0 in postpartum care, delivery care, newborn, family planning there are no gaps. Conclusion Comprehensive midwifery care for Mrs. I GIP0A0 ​​aged 26 years old Mrs. I G1P0A0 pregnancy care in postpartum care, delivery care, newborn, family planning there are no gaps and Suggestions given to the health service, educational institutions, practice areas, and the community to further improve health services in accordance with Midwifery care standards.